2023
DOI: 10.3390/jcm12103440
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Newly Developed Guidewire for Selective Biliary Cannulation: A Multicenter Randomized Controlled Trial

Abstract: Background and Aims: Various guidewires are used for biliary cannulation, and each one has its own characteristics affecting its effectiveness. This study aimed to measure the basic properties and evaluate the effectiveness of a newly developed 0.025-inch guidewire for selective biliary cannulation. Methods: A total of 190 patients at five referral hospitals were randomly allocated to undergo selective biliary cannulation using the newly developed guidewire (NGW group, n = 95) or a conventional guidewire (CGW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrast, experimental studies may be helpful for objective assessment of clinical performance of guidewires. Recently, five studies involving experiments to evaluate guidewire performance have been reported [5,6,9,10,11]. In these studies, several guidewire products were examined and compared regarding clinical performance, ▶…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, experimental studies may be helpful for objective assessment of clinical performance of guidewires. Recently, five studies involving experiments to evaluate guidewire performance have been reported [5,6,9,10,11]. In these studies, several guidewire products were examined and compared regarding clinical performance, ▶…”
Section: Discussionmentioning
confidence: 99%
“…The 0.025-inch guidewires used for ERCP and EUS-BD are required to have the following clinical performance: good seeking ability, lubricity, flexible tips, and stiff shafts. Several studies have evaluated these characteristics of specific guidewire products [5,6,9,10,11]. However, those studies primarily focused on comparisons among guidewire products and lacked a structural perspective that could be useful for guidewire development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation